Distribution of brain sodium accumulation correlates with disability in multiple sclerosis: a cross-sectional 23Na MR imaging study - Zaaraoui, Wafaa; Konstandin, Simon; Nagel, Armin Michael; Schad, Lothar R. (Radiology, 2012)
PurposeTo quantify brain sodium accumulations and characterize for the first time the spatial location of sodium abnormalities at different stages of relapsing-remitting (RR) multiple sclerosis (MS) by using sodium 23 (23Na) magnetic resonance (MR) imaging.Materials and MethodsThis study was approved by the local committee on ethics, and written informed consent was obtained from all participants. Three-dimensional 23Na MR imaging data were obtained with a 3.0-T unit in two groups of patients with RR MS—14 with early RR MS (disease duration <5 years) and 12 with advanced RR MS (disease duration >5 years)—and 15 control subjects. Quantitative assessment of total sodium concentration (TSC) levels within compartments (MS lesions, white matter [WM], and gray matter [GM]) as well as statistical mapping analyses of TSC abnormalities were performed.ResultsTSC was increased inside demyelinating lesions in both groups of patients, whereas increased TSC was observed in normal-appearing WM and GM only in those with advanced RR MS. In patients, increased TSC inside GM was correlated with disability (as determined with the Expanded Disability Status Scale [EDSS] score; P = .046, corrected) and lesion load at T2-weighted imaging (P = .003, corrected) but not with disease duration (P = .089, corrected). Statistical mapping analysis showed confined TSC increases inside the brainstem, cerebellum, and temporal poles in early RR MS and widespread TSC increases that affected the entire brain in advanced RR MS. EDSS score correlated with TSC increases inside motor networks.ConclusionTSC accumulation dramatically increases in the advanced stage of RR MS, especially in the normal-appearing brain tissues, concomitant with disability. Brain sodium MR imaging may help monitor the occurrence of tissue injury and disability.© RSNA, 2012Supplemental material: http://radiology.rsna.org/lookup/suppl/doi:10.1148/radiol.12112680/-/DC1
Gesehen am 21.08.2018